2021
DOI: 10.1017/qua.2021.24
|View full text |Cite
|
Sign up to set email alerts
|

Species distribution modeling reveals the ecological niche of extinct megafauna from South America

Abstract: Climatic and environmental changes, as well as human action, have been cited as potential causes for the extinction of megafauna in South America at the end of the Pleistocene. Among megamammals lineages with Holarctic origin, only horses and proboscideans went extinct in South America during this period. This study aims to understand how the spatial extent of habitats suitable for Equus neogeus and Notiomastodon platensis changed between the last glacial maximum (LGM) and the middle Holocene in order to deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…It was developed along the Permian suture of the Patagonia terrane with Western Gondwana (Ramos, 1984 ; Suárez et al., 2019 ), which may have acted as a kind of environmental barrier that seems to have had some influence on the distribution of M. ruber . Studies focused on South American megafauna, for example, have already reported the nonoccurrence of certain species below this latitude (Araújo et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was developed along the Permian suture of the Patagonia terrane with Western Gondwana (Ramos, 1984 ; Suárez et al., 2019 ), which may have acted as a kind of environmental barrier that seems to have had some influence on the distribution of M. ruber . Studies focused on South American megafauna, for example, have already reported the nonoccurrence of certain species below this latitude (Araújo et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard as it applies to the PPM, it would be instructive to reconsider approaches on the vulnerability to and causes and timing of extinction (e.g., Lessa & Fariña, 1996;Lessa et al, 1997;Cione et al, 2003Cione et al, , 2009Cione et al, , 2011Prado et al, 2015) in light of the keystone megafauna definition, and those on paleoecology (e.g., Fariña, 1996;Prevosti & Vizcaíno, 2006;Fariña et al 2014) in light of functional and apex megafauna. Paleoecology and extinction can be related topics and treated in the same article (e.g., Vizcaíno et al, 2012), or the research can be focused on other issues such as the fossil record (e.g., Marshall et al, 1984;Prado et al, 2021), biogeography or species distribution modeling (e.g., Varela et al, 2018;Araújo et al, 2021). In these cases, clarification of the criteria on which the term megafauna is based is warranted.…”
Section: The Concept Of Megafaunamentioning
confidence: 99%
“…Indeed, it has been argued that the loss of prey species led to large predators going extinct in the Late Pleistocene [26,27]. Although the arrival of modern humans and/or climate change have been identified as the most likely ultimate causes of megafauna extinctions in the Late Pleistocene, vegetation change associated with human arrival and/or climate change has been identified as a pathway through which these ultimate causes could have triggered extinctions (i.e., via bottom-up trophic cascades) [2831].…”
Section: Introductionmentioning
confidence: 99%